دور الأمثال الشعبية السوفية في نقد السلوك الجماعي – دراسة في ضوء المنهج النفسي - بحري, هندة; عميار, منى (جامعة الوادي - University of Eloued, 2023)
إن المثل دستور حياة وقانونها نابع من ذات المجتمع، يترعرع داخله حتي يكبر وينضج، ليكون قاعدة يسير عليها الفرد داخل نظام واحد في كافة تخصصات الحياة . وتهدف دراستنا لدور الأمثال الشعبية السوفية في نقد السلوك الجماعي ، دراسة في ضوء المنهج النفسي من اجل اثبات ان الأمثال الشعبية السوفية غنية بالفنون البلاغية والموضيع الاجتماعية ، تصلح لدراسات حول هذا الارث الادبي الذي ورثناه عن اجدادنا واردنا الحفاظ عليه. The proverb is a constitution of life and its law stems from the same society, within which it grows until it grows and matures, to be a rule upon which the individual follows within a single system in all disciplines of life. Our study aims at the role of Soviet proverbs in criticizing collective behavior, a study in the light of the psychological approach in order to prove that Soviet proverbs are rich in rhetorical arts and social topics, suitable for studies on this literary legacy that we inherited from our ancestors and we wanted to preserve it.
أدب شعبي
Keywords: الامثال - وادي سوف – الشعبية; proverbs - Wadi Souf - popular